The ‘supernatural existential’ in the foundations of christian faith of Karl Rahner - Danso Abeam, Emmanuel (2021)
The main purpose of this dissertation is to study the concept of the ‘supernatural existential’ in Karl Rahner’s Foundations of the Christian Faith: An Introduction to the Idea of Christianity. In order to study this concept we first study the meaning of ‘existential’, and secondly of ‘supernatural’ as self-communication of God. Thus, when Rahner speaks of ‘existential’, he is talking about the fundamental elements of human existence. The ‘one’ who can hear the self-communication of God. Secondly, when Rahner speaks of ‘supernatural’ he means that «God in his own most proper reality makes himself the innermost constitutive element of man». In other words, God communicates His very life to the human being. Thus the technical term ‘supernatural existential’ in Rahner means the communication of the very being of God to the human being. The aim of this dissertation is to clarify how important it is for a human being to accept God’s free and forgiving self-communication in his life. It also brings to mind the pastoral sense of this concept. By this we mean the seriousness of Christian responsibility and evangelization.